How American-based television commercials portray convicts, correctional officials, carceral institutions, and the prison experience - Ross, Jeffrey Ian (Corrections, 2018)
The manner in which deviant and marginalized groups are portrayedin popular culture shapes public perceptions and policy responses.These messages are communicated through a variety of channels.Over the past decade, scholarly interest in the portrayal of prisoners,correctional officers, and correctional institutions has increased. Oneof the unexplored, important, and relatively contemporary mediumsthrough which inmates, correctional officers, and carceral spaceshave been portrayed is through commercials. These messages appearvia print, television, and the Internet. In an attempt to understand thecontent and context of these commercials, the following article pre-sents the results of a content analysis of American-based televisioncommercials that feature convicts, correction officials, prison settings,and/or the carceral experience.